Analysis Juridical Notary Role Of Acquisition Of Assets Of The Debtor As An Alternative Solution Loan Loss (Case Study In Bank BNI Branch Semarang) - Muhammad Wildan Mahindra; Ardi Sanditya; Munsharif Abdul Chalim (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
Banking development shows the dynamics of economic life. Prior to the practice that happens, a lot of problems that arise in the banking one of which is the number of cases of problem loans up to be a bad credit, this raises the firmness of the banks in the lending process. The acquisition made a lot of pros and cons between the customer and the Bank Negara Indonesia (BNI) Branch SemarangThe purpose of this study was to know and analyze the completion of the takeover of Bad Debts Mortgage Assets, identify and analyze the role of the Notary on Takeover Process Mortgage collateral and to know and analyze the obstacles that occur in the process of the takeover of mortgage collateral and settlement with Bank Negara Indonesia (BNI).This study using sociological juridical approach, the specification is descriptive analytical research, data sources used in the form of primary data obtained through interviews, secondary data with the literature study, qualitative analysis. The problem is analyzed using the theory of implementation and effectiveness of the rule of law.Based on the results of this study concluded that: 1) The need for a significant settlement between the banks by the debtor in the case of bad credit, the need for new regulations in Credit rescue to prevent possible lossesin a way Rescheduling, re requirements, reordering,2) The role of the Notary, in making this agreement directs, bank at Bank Indonesia Regulation (PBI) on Lending Limit for Commercial Banks and the guidelines for the general bank credit policies SoRegarding intervention of the notary bank credit agreement which refers to the bank's internal rules respectively for the 3) Barriers to solve the problem in bad debts suggesting there should be a code of conduct so that no authority notary public notary so not tricked by the bank.Keywords: Bad Debt; Foreclosure Of Collateral; Notary Role.